Active surveillance: a potential strategy for select patients with small renal masses. (October 2011) - Smaldone, Marc C; Uzzo, Robert G
Increased abdominal imaging has led to the significant incidental detection of clinically localized renal masses. While the gold standard remains surgical excision, mortality rates from kidney cancer remain relatively unchanged implying that a proportion of small renal masses may be indolent tumors that do not require surgical intervention. As a result, active surveillance has emerged as an alternative management strategy in select patients with significant competing risks. Although the contemporary literature characterizing the natural history of untreated small renal masses is limited, recent data demonstrate that many incidental renal masses demonstrate slow growth kinetics with a low rate of progression to metastatic disease over an intermediate time period. Prospective trials are necessary to define entry and intervention criteria for active surveillance protocols.